Peran Hukum Ekonomi Syariah Dalam Mendorong Kewirausahaan di Indonesia - Yoesvizar, Salsabila Amalia Putri; B, Baidhowi (Media Hukum Indonesia (MHI), 2025)
Sharia economic law has become a crucial pillar in the development of the economy in Indonesia, particularly in the context of entrepreneurship. This article aims to analyze the role of sharia economic law in promoting the growth of entrepreneurship in Indonesia, focusing on the fundamental sharia principles underlying economic transactions. Through a qualitative approach, this study explores various sharia financing products, such as murabahah, musyarakah, and mudharabah, which provide better financing access for entrepreneurs, especially among communities underserved by conventional financial systems. Additionally, this article discusses the challenges faced in implementing sharia economic law and provides recommendations to enhance understanding and application of sharia principles in the entrepreneurial world. The research findings indicate that sharia economic law not only contributes to increased access to financing but also promotes innovation and sustainability in entrepreneurial practices. Thus, the role of sharia economic law is highly significant in creating and realizing an inclusive and sustainable entrepreneurial ecosystem in Indonesia